Pharmacokinetic analysis of drugs vitamin D for oral administration - I. Yu. Torshin; O. A. Gromova; D. E. Frolova; T. R. Grishina; N. P. Lapochkina (LLC "Publisher OKI", 2019)
In the group of healthy volunteers (women 24-53 years, n = 12) pharmacokinetic curves of levels 25(OH)D and 1,25(OH)D in the blood for two dosage forms of oil solution - the drug Vigantol (n = 6) and chewing tablets - Ultra-D (n = 6) were obtained. Each drug was taken once in a dose of 10,000 IU, then blood sampling was carried out for 6 hours. The multichamber and tubeless pharmacokinetic analysis of the collected data was carried out. It was found that both drugs are characterized by comparable indicators of pharmacokinetics. For example, for the Ultra-D tubeless analysis allowed us to estimate the values of Cmax = 28 ± 4 ng/ml, tmax = 50 ± 15 min, Clast = 20 ± 1 ng/ml, for other uses = 8586 ± 693 ng/ml*min, MRTt = 170 ± 4 min, Lz = 0.00087 ± 0.0004 inch rnin-1, T1/2 = 15.5 ± 7.2 h, CL = 7 ± 2 ml/min, Vd = 9.04 ± 1.24 L. Thus, after taking chewable tablets, the area under the curve (indicator for other uses) characterizing the bioavailability, was significantly higher. This is due to the fact that the components of saliva accelerate absorption, since the solubilization of molecules of cholecalciferol begins already in the oral cavity. The pharmacokinetic parameters obtained were practically independent of the age of the volunteers. At the same time, significant correlations of pharmacokinetic parameters with initial levels of 25(OH)D in blood were established. Multi-chamber pharmacokinetic analysis showed that the obtained pharmacokinetic curves with a high degree of confidence correspond to the multi-chamber model, which includes three compartments: "GI", "Central blood circulation" and "depot 25(OH)D".